Critical incidents in intercultural education lessons - de Diesbach-Dolder, Stéphanie; Muller Mirza, Nathalie (Swiss Journal of Educational Research, 2022)
This article is based on the results of a research on real teaching practices in intercultural education. Based on the considerations highlighted in the literature about the risks of "culturalization" of these practices, this contribution aims to understand how difficulties emerge, develop, and even transform themselves in classroom interactions. On the basis of pedagogical sequences collected in class during intercultural lessons, we identify critical incidents that allow us to identify the tensions between, on the one hand, the pedagogical intentions of the teachers, which aim at building knowledge and deconstructing phenomena such as social discrimination or stereotypes, and, on the other hand, the interactive process of constructing meanings which sometimes results in their reification.